Determination of Trans-Resveratrol Levels in Different Fruits, Vegetables and Their Skin by HPLC - Arslan, Gulsen; Yilmaz, Necmettin (Asian Journal of Chemistry, 2012)
The aim of this study is to identify and compare the amount of resveratrol in various fruits, vegetables and their skin or shell. Resveratrol levels in samples were measured using HPLC. Some of the samples did not show a presence of resveratrol while a significant amount was detected in the remainder of samples. The analysis results showed that the resveratrol levels were high in peanut (Arachis hypogaea) shell (39.1 μg/g), black mulberry fruit (Morus nigra) (32.5 μg/g), red grape (Vitis vinifera) seed (28.0 μg/g), cucumber (Cucumis sativus) skin (18.0 μg/g), and cherry laurel fruit (1.50 μg/g). Results indicate that some fruits and vegetables tested here could be consumed as a resveratrol source.